Psikoanalisis Dalam Cantik Itu Luka Karya Eka Kurniawan - Indah Wening (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
This paper aims to describe the sexual behavior of the five female characters in Cantik itu Luka by Eka Kurniawan using a psychoanalytic approach. These five female characters are related by blood, but have different sexual behaviors. Psychoanalysis brought this research to see the text in literary works as manifest texts, then the ideology of the author that is disguised and displayed in literary works is called latent text. Thus, this paper is expected to be able to present something that belongs to the subtext. Oedipus complex, narcissism, castration, dreams, fantasticism, and mythology greatly influence the sexuality behavior of these five figures.